2014
DOI: 10.1186/1472-6882-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine Guizhi Fuling Formula for treatment of uterine fibroids: a systematic review of randomised clinical trials

Abstract: BackgroundGuizhi Fuling Formula is widely applied for uterine fibroids in China. Many clinical trials are reported. This study assessed the efficacy and safety of Guizhi Fuling Formula for the treatment of uterine fibroids.MethodsPubMed, Cochrane CENTRAL, EMBASE, and four Chinese databases were searched through May 2013. We included randomised controlled trials (RCTs) that tested Guizhi Fuling Formula for uterine fibroids, compared with no intervention, placebo, pharmaceutical medication, or other Chinese pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), when given for symptom relief, has gained widespread popularity among women with PD [2]. The typical prescriptions of TCM for the treatment of PD are reported as Gegen Decoction, Danggui Shaoyao San, Siwu Tang, Guizhi Fuling Wan, Guizhi Fuling Capsule and so on [6][7][8], which could exert synergistic therapeutic efficacies through multiple regulating humoral immunity and cellular immunity, and releasing inflammatory response [16,17]. In our previous investigation, the bioactive ingredients absorbed into the rat plasma were analyzed, we screened out six ingredients, including gallic acid (from Paeoniae Radix Alba), amygdalin (from Persicae Semen), albiflorin (from Paeoniae Radix Alba), paeoniflorin (from Paeoniae Radix Alba), paeonol (from Moutan Cortex), cinnamic acid (from Cinnamomi Ramulus) which exhibited significant correlation of drug concentration-time curve in rat plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), when given for symptom relief, has gained widespread popularity among women with PD [2]. The typical prescriptions of TCM for the treatment of PD are reported as Gegen Decoction, Danggui Shaoyao San, Siwu Tang, Guizhi Fuling Wan, Guizhi Fuling Capsule and so on [6][7][8], which could exert synergistic therapeutic efficacies through multiple regulating humoral immunity and cellular immunity, and releasing inflammatory response [16,17]. In our previous investigation, the bioactive ingredients absorbed into the rat plasma were analyzed, we screened out six ingredients, including gallic acid (from Paeoniae Radix Alba), amygdalin (from Persicae Semen), albiflorin (from Paeoniae Radix Alba), paeoniflorin (from Paeoniae Radix Alba), paeonol (from Moutan Cortex), cinnamic acid (from Cinnamomi Ramulus) which exhibited significant correlation of drug concentration-time curve in rat plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Its traditional effects are invigorating blood, resolving masses, and dissolving stasis [8]. To assess the efficacy and safety of GZFLC for the treatment of uterine leiomyomas, Chen et al identified 38 randomized controlled trials involving 3816 participants by meta-analyses [11] and found that GZFLC plus mifepristone was more effective than mifepristone alone in reducing the volume of uterine leiomyoma. GZFLC significantly improved symptoms of uterine leiomyoma, particularly in dysmenorrhea, when it was used alone or in combination with mifepristone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used for the treatment of different diseases such as gynecological diseases and atherosclerosis [8, 9] and is involved in multiple pharmacological activities, such as stimulating the proliferative lesion soft and absorption, enhancing immune response, and preventing cancer cell growth [10]. In recent years, a clinical research confirmed that GZFLC was effective in uterine leiomyomas [11, 12]. GZFLC, the clinical recommended regimen, is taken orally as 3 capsules (in total 0.93 g) at one time, 3 times per day, 3 to 6 months, used alone or combined with mifepristone, GnRH-a, or other drugs to treat uterine leiomyomas.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 100,000 formulas for disease therapy in China [12]. A large number of compounds have been isolated from TCMs and most of them have not yet been characterized for the development of new drugs [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%